THE EFFICACY OF THE ARBITRATION CLAUSE IN A SIMULATED ACT - Tudor Vlad RĂDULESCU (Challenges of the Knowledge Society)
The article focuses on the effects that an arbitration clause can still produce when it is contained in a simulated operation, whether it is in the apparent act or in the secret one, depending on the forms of simulation.